2011
DOI: 10.1103/physreva.84.062330
|View full text |Cite
|
Sign up to set email alerts
|

Security problem on arbitrated quantum signature schemes

Abstract: Until now, there have been developed many arbitrated quantum signature schemes implemented with a help of a trusted third party. In order to guarantee the unconditional security, most of them take advantage of the optimal quantum one-time encryption method based on Pauli operators. However, we in this paper point out that the previous schemes only provides a security against total break and actually show that there exists a simple existential forgery attack to validly modify the transmitted pair of message and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 21 publications
0
63
0
Order By: Relevance
“…Whether these countermeasures can overcome all the security problems discovered in Refs. [7][8][9][10] and how to design an AQS scheme which can withstand existing or potential attacks deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these countermeasures can overcome all the security problems discovered in Refs. [7][8][9][10] and how to design an AQS scheme which can withstand existing or potential attacks deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…Alice uses single qubit rotation operators for the generation of the redundant message and the signature operation. The generated signature pair is encrypted by using (I, H )-type quantum encryption [38]. Receiving the encrypted signature pair from Alice, TC keeps the redundant message and sends the signature to Bob.…”
Section: Quantum Signature Scheme Using a Single Qubit Rotation Operatormentioning
confidence: 99%
“…TC receives signature pair sign A and h (I D r ) from Alice and obtains |S A and |R A by decrypting sign A as follows [38] ⊗…”
Section: Preparation Phasementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been shown that it could be possible to quantumly sign quantum messages with the assistance of an arbitrator, which is called the arbitrated quantum signature (AQS) [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%